2007
DOI: 10.1016/j.ophtha.2007.05.062
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Randomized Clinical Trial of Intravitreal Bevacizumab for Diabetic Macular Edema

Abstract: Objective-To provide data on the short-term effect of intravitreal bevacizumab for diabetic macular edema (DME). Design-Randomized phase 2 clinical trial.Participants-121 eyes of 121 subjects (109 eligible for analysis) with DME and Snellen acuity equivalent ranging from 20/32-20/320.Interventions-Random assignment to one of five groups: focal photocoagulation at baseline (N=19, Group A), intravitreal injection of 1.25mg bevacizumab at baseline and 6 weeks (N=22, Group B), intravitreal injection of 2.5mg bevac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(127 citation statements)
references
References 23 publications
2
122
0
3
Order By: Relevance
“…There have been several studies showing improvement in VA as well as reduction in macular edema in patients treated with intravitreal anti-VEGF agents, especially bevacizumab, against DME [12,13,14,15,16,17,18,19,20,21,22]. Recent studies have also demonstrated that ranibizumab, another anti-VEGF agent, exhibited a positive effect on DME [6,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies showing improvement in VA as well as reduction in macular edema in patients treated with intravitreal anti-VEGF agents, especially bevacizumab, against DME [12,13,14,15,16,17,18,19,20,21,22]. Recent studies have also demonstrated that ranibizumab, another anti-VEGF agent, exhibited a positive effect on DME [6,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Triamcinolone is a multiple-potency drug, including an anti-inflammatory and an anti-VEGF effect, with a longer intraocular half-life, compared with bevacizumab [5,6,7,8]. On the other hand, bevacizumab, a humanized monoclonal antibody blocking all isoforms of VEGF, has been found to be relatively free of intraocular complications associated with the requirement for more frequent injections in order to maintain its effects [9,10,11,12,13]. In addition, intravitreal injection of bevacizumab combined with triamcinolone was also considered and was reported to have a short-term beneficial effect on DME [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…В исследовании было определено, что при отсутствии КЗМО лечение методом лазерной коагуляции неэффек-тивно, а наиболее подходящее время для проведения фокальной лазерной терапии -это момент появления клинически значимого ДМО [39].…”
Section: лечение методом лазерной коагуляцииunclassified